The principle of the dignity of human person: a reading of the effectiveness of citizenship and human rights through the challenges put forward by globalization - Mezzaroba, Orides; Oliveira da Silveira, Vladmir (Revista de Investigações Constitucionais, 2018)
Even today concepts that should have been overcome are debated, for example, the belonging of an individual to a State and, consequently, to its laws. The process of globalization, and the constant immigration resulted thereof, have led to profound changes in the relationship between the individual and the State, and especially, in the field of international human rights law. This means that the human needs began to be manifested regionally and internationally, in order to achieve the principle of the dignity of the human being. Thus, this article intends to investigate the link between citizenship and human rights, from new perspectives, through literature studies and deductive method, in order to answer the following questions: what are the added values to the concept of citizenship? And what is the current dimensions of citizenship?